World's first commercial bridge capacitor bank installation on the American Electric Power System. - Andrei, R.G (IEEE Transactions on power delivery)
The paper presents some of the engineering aspects of the first commercial installation of a bridge capacitor bank on the American Electric Power System. System performance and the economic aspects of the installation, which went in service on November 1998, are also discussed